Impact of body mass index as a continuous variable on short‐ and long‐term outcomes in patients undergoing laparoscopic surgery for colon cancer - Takayuki Aiba; Tomonori Akagi; Hidefumi Shiroshita; Kentaro Nakajima; Tetsuji Ohyama; Tatsuya Kinjo; Akiyoshi Kanazawa; Nobuaki Suzuki; Takuya Tokunaga; Manabu Yamamoto; Nobuki Ichikawa; Shungo Endo; et al. (Annals of Gastroenterological Surgery)
Abstract Background The impact of obesity on colon cancer remains unclear. Very few studies of colon cancer surgery have analyzed body mass index (BMI) as a continuous variable, with no such reports from Japan. This study examined the association between BMI as a continuous variable and short‐ and long‐term outcomes of laparoscopic surgery for obese colon cancer patients. Methods Obese (BMI ≥25 kg/m2) patients who underwent laparoscopic radical surgery for Stage II/III colon cancer at 46 participating centers from 2009 to 2013 were included. Associations between short‐ and long‐term outcomes and BMI as a continuous variable were analyzed by univariate and multivariate regression models. Results Among patients meeting the study criteria, 1036 were examined. BMI as a continuous variable correlated with log‐transformed operative time (regression coefficient: 0.02, 95% confidence interval [CI]: 0.012–0.028, p < 0.05) and blood loss (odds ratio: 1.089, 95% CI: 1.032–1.149, p < 0.05). There was no association between BMI continuous variables and 3‐year relapse‐free survival (RFS) and overall survival. However, 3‐year RFS was possibly better in patients with BMI ≥28.5 kg/m2 versus those with BMI <28.5 kg/m2 (hazard ratio: 0.682, 95% CI: 0.462–1.008, p = 0.055). Conclusions This study showed that BMI as a continuous variable correlated with operative time and blood loss. RFS was possibly better in the severely obese patients (BMI ≥28.5 kg/m2), suggesting that the prognosis for highly obese colon cancer patients appears to follow the obesity paradox.